2002
DOI: 10.3233/nre-2002-17302
|View full text |Cite
|
Sign up to set email alerts
|

Return to work after spinal cord injury: A review of recent research

Abstract: This manuscript reviews recent research on return to work (RTW) for individuals who sustain spinal cord injury (SCI), including the effects of demographics variables, occupational characteristics, workplace accommodations, quality of life, physical functional limitations, and other variable. Demographic variables that influence RTW for persons with SCI include age at injury onset, chronological age, gender, education, ethnicity, marital status, and per-injury work intensity. Others include satisfaction, and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 48 publications
(94 reference statements)
3
30
0
Order By: Relevance
“…It is reported that the probability of employment after SCI improves with increasing time since injury (20,21). Persons who incur their SCI at an older age are much less likely than younger persons to return to work (44). Furthermore, persons injured during adulthood have lower reported employment rates and physical functioning vs those injured in childhood (50).…”
Section: Sci and Vocational Outcomes Rates Of Employment After Scimentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that the probability of employment after SCI improves with increasing time since injury (20,21). Persons who incur their SCI at an older age are much less likely than younger persons to return to work (44). Furthermore, persons injured during adulthood have lower reported employment rates and physical functioning vs those injured in childhood (50).…”
Section: Sci and Vocational Outcomes Rates Of Employment After Scimentioning
confidence: 99%
“…The influence of sex on obtaining employment has shown mixed results. In many cases, men have been found more likely to return to work (3,(56)(57)(58)(59)(60), whereas in some cases, women have been found more likely to be employed after SCI (2,44,49) When type of work is considered, it has been found that men are more likely to return to competitive (paid) employment, whereas women are more likely to be engaged in nonpaid, productive roles (eg, homemaker) (61). However, in a large sample of individuals with SCI in 2 regions of the United States, sex was not predictive of employment status based on logistic regression analyses (8).…”
Section: Sci and Vocational Outcomes Rates Of Employment After Scimentioning
confidence: 99%
“…Employment is associated with better functioning, social integration (1,2), better quality of life and adjustment (2)(3)(4), psychological wellbeing (1) and lower mortality (5,6). nevertheless, there are significant barriers to gaining and maintaining employment (7,8). Employment figures range from 21% to 67% (7) and a mean of only 35-40% of individuals with SCI are in paid employment (6).…”
Section: Introductionmentioning
confidence: 99%
“…This paper expands on previously reported findings 21 by Fitzharris et al 21 The study of 62 patients admitted to hospital specifically excluded those with moderate or severe head injury and spinal cord injury due to well stated rehabilitation challenges associated with these injuries. 5,16,25 In elaborating on these findings, the aim of this paper is to explore the relationships between injury type, disability, work role and RTW rates.…”
mentioning
confidence: 99%